Soluble CD147 regulates endostatin via its effects on the activities of MMP-9 and secreted proteasome 20S - Rahat, Maya M.; Sabtan, Hala; Simanovich, Elina; Haddad, Amir; Gazitt, Tal; Feld, Joy; Slobodin, Gleb; Kibari, Adi; Elias, Muna; Zisman, Devy; Rahat, Michal A. (Frontiers in Immunology, 2024)
During progression of Rheumatoid arthritis (RA), angiogenesis provides oxygen and nutrients for the cells' increased metabolic demands and number. To turn on angiogenesis, pro-angiogenic factors must outweigh anti-angiogenic factors. We have previously shown that CD147/EMMPRIN can induce the expression of the pro-angiogenic factors VEGF and MMP-9 in a co-culture of the human HT1080 fibrosarcoma and U937 monocytic-like cell lines. However, whether CD147 influences anti-angiogenic factors was not known. We now show that relative to single cultures, the co-culture of these cells not only enhanced pro-angiogenic factors but also decreased the anti-angiogenic factors endostatin and thrombospondin-1 (Tsp-1), generally increase the angiogenic potential as measured by the wound assay. Using anti-CD147 antibody, CD147 siRNA and recombinant CD147, we demonstrate that CD147 hormetically regulates the generation of endostatin, but has no effect on Tsp-1. Since endostatin is cleaved from collagen XVIII (Col18A), we applied different protease inhibitors and established that MMP-9 and proteasome 20S, but not cathepsins, are responsible for endostatin generation. MMP-9 and proteasome 20S collaborate to synergistically enhance endostatin generation, and in a non-cellular system CD147 enhanced MMP-9 activity and hormetically regulated proteasome 20S activity. Serum samples obtained from RA patients and healthy controls mostly corroborated these finding, indicating a clinical relevance. Cumulatively, these findings suggest that secreted CD147 mediates a possibly allosteric effect on MMP-9 and proteasome 20S activities, and can serve as a switch that turns angiogenesis on or off, depending on its ambient concentrations in the microenvironment.